Internalization of Qur'anic Values in Shaping Students' Character - M. Munif (International Journal of Islamic Pedagogical Research, 2025)
Character education in Islamic schools requires a systematic integration of Qur’anic values to shape students’ moral, spiritual, and social behavior. Despite widespread recognition of its importance, the implementation strategies for internalizing these values remain varied and context-dependent. This study aims to systematically review existing literature to identify effective strategies for the internalization of Qur’anic values in schools and their impact on student character development. A systematic literature review (SLR) was conducted by analyzing peer-reviewed journal articles, books, and educational reports related to Qur’anic-based character education. Inclusion criteria focused on studies that explored pedagogical strategies, school culture, and extracurricular programs in Islamic educational contexts. Data were synthesized to categorize strategies, outcomes, and theoretical underpinnings. The review identifies four major strategies for internalizing Qur’anic values: (1) Qur’an-based learning integrated across subjects, active reflection, and experiential methods; (2) structured daily worship routines, flagship character programs, and value-rich school environments; (3) role modeling by teachers and leadership guidance from school principals; and (4) extracurricular activities, social engagement, and Qur’anic-based leadership programs. Implementation of these strategies positively influences students’ moral reasoning, discipline, spiritual awareness, and social responsibility. The findings highlight the crucial role of teachers, school leadership, and family-community collaboration in sustaining a Qur’anic value-centered educational ecosystem. This study provides a comprehensive framework for educators and policymakers to design holistic programs that promote character development grounded in Qur’anic teachings, offering practical insights for enhancing spiritual, moral, and social competencies in students.